Sol-gel Synthesis, Structural and Characterization of Ag-Gd-Ti-O Nanocomposites - Ramesh, S.; Das, B.B. (Asian Journal of Chemistry, 2012)
The Ag3(2+x)GdxTi4-xO11+d (0.0 £ x £ 1.0) (x = 0, 0.25, 0.5, 0.75 and 1.0) nanocomposites were successfully synthesized by sol-gel technique. The surface morphology, structure and the properties of nanocomposites were investigated by SEM, XRD, UV, EPR and VSM. The XRD result reveals that the composites were formed in tetragonal lattice type with P42/nnm space group. The average crystallite size of the composites varied from 44 nm to 63 nm. The surface morphology of the samples was evaluated by SEM. The purity of the composites was confirmed through the energy dispersive X-ray analysis. Electron paramagnetic resonance line shapes were recorded at 8, 77 and 300 K, which are isotropic in nature. The magnetic susceptibility values of the samples are in ferromagnetic nature at room temperature.